Gambaran Pengetahuan Remaja Putri tentang Genitalia Hygiene saat Menstruasi pada Siswi Kelas IX di SMP Negeri 3 Takalar Tahun 2024 - Yahya, Fajar Dhini; Hartuti, Noviyani (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan Pelamonia, 2024)
Abortion remains a leading cause of maternal death in Indonesia, with anemia considered a contributing risk factor. This study aimed to determine the relationship between anemia and abortion among pregnant women at RSUD Padjonga Dg. Ngalle, Takalar Regency. This was an analytical study with a cross-sectional approach involving 202 pregnant women selected through random sampling from a total population of 409. Secondary data were obtained from medical records and analyzed using the Chi-Square test. The results showed that all 54 anemic women experienced abortion, while most non-anemic women did not. Statistical analysis showed a significant relationship with a p-value of 0.000 (p < 0.05). It is concluded that anemia increases the risk of abortion in pregnant women.